(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
It is known as hozirgi at the time village resources directory asinxron who consumed three-phase reactive power main engines, transfarmatorlar, electric power transmission lines and gazorazryidli lamps. Agricultural enterprises using a device used to feed the crushingengines sinxroni reactive power 60 – 80% of the consumption[1-17].